Difficulties of unit managers in selected district hospitals in Cameroon - Esther L. Wanko Keutchafo; Jane Kerr (AOSIS, 2019)
Background: Being appointed to a managerial position because of one's clinical skills seems to be prestigious, even powerful. However, being a unit manager in a resource-constrained district hospital can be a daunting task. Also, managing a ward unit with no previous training in leadership and management can be very challenging. Objectives: The purpose of this study was to describe the difficulties, in the day-to-day activities, of unit managers in selected Cameroonian district hospitals. Method: A constructionist, descriptive Husserlian phenomenological inquiry was conducted to describe the difficulties of unit managers in two district hospitals. Ten unit managers were selected through a purposive sampling scheme, and then interviewed using semi-structured interviews. Coliazzi's qualitative data analysis method was used for analysis. Results: This study revealed that unit managers looked for assistance because it is not easy to be in their position. Their role implied facing difficulties and making sacrifices for something that is not even worth the trouble. Therefore, as a way to overcome their difficulties, they asked for assistance from the organisation, from their families and from God as strategies to face their difficulties. Conclusion: The difficulties faced by unit managers in the selected district hospitals revealed the need to prepare nurses for managerial positions by ensuring they are trained as managers before commencing employment as a manager.